1980
DOI: 10.1136/bmj.280.6206.7
|View full text |Cite
|
Sign up to set email alerts
|

Venous lipodermatosclerosis: treatment by fibrinolytic enhancement and elastic compression.

Abstract: Summary and conclusionsThe value of fibrinolytic enhancement with an anabolic steroid (stanozolol) combined with elastic stockings in treating venous lipodermatosclerosis was assessed in a six-month double-blind cross-over trial. Thirty-four legs of 23 patients in whom other treatments had failed were studied. The patients were randomly divided into two groups who were treated with either stanozolol plus elastic stockings or placebo plus elastic stockings for three months, and then vice versa. Treatment with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0
1

Year Published

1987
1987
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(57 citation statements)
references
References 2 publications
0
55
0
1
Order By: Relevance
“…The anabolic steroid stanozolol may be helpful in some patients [1, 9], but not in others [10]. It has been reported that antibiotics, various anti-inflammatory agents, antimetabolites and surgery have been used with limited or non success [1].…”
Section: Discussionmentioning
confidence: 99%
“…The anabolic steroid stanozolol may be helpful in some patients [1, 9], but not in others [10]. It has been reported that antibiotics, various anti-inflammatory agents, antimetabolites and surgery have been used with limited or non success [1].…”
Section: Discussionmentioning
confidence: 99%
“…Although the healing rate was twice that of the placebo, the results did not reach statistical significance. 107 No adverse clinical effects were noted during the 3-month clinical trial.…”
Section: Drug Therapymentioning
confidence: 99%
“…Although its use has been relatively widespread, in [3] and arteriosclerotic disease [4], the exact modes of action of this compound have been unclear. Stanozolol has been shown to stimulate fibrinolytic activity [5] which could explain some of its actions, for example, the increased breakdown of fibrin in conditions such as rheumatoid arthritis [6].…”
Section: Introductionmentioning
confidence: 99%